KERENTANAN TERPAPAR HIV PADA PEREMPUAN PENGHUNI PENJARA - Benita Nastami (Jurnal Kriminologi Indonesia, 2012)
Overcrowding has always been common problem that happens in Indonesia’s prison. This leads to other problems such as being risk to HIV exposure while they are in the prison. Moreover the society and government has not keep attention on prison population healthy condition. The government had responsibility to fulfill their rights and such as to get healthy services. But it is difficult to give them their rights while the condition of overcrowding exist. The problem then being analyzed using prison concept execution, overcrowding and its problem, women in prison, HIV/AIDS in prison, and sufficient health rights for inmates framework. This research use field research method with depth interview and observation techniques in Lapas Bogor. Conclusion of this research is there that is little vulnerability condition in prison (Lapas Bogor) that has put the inmates in the vulnerable position to exposed with HIV while they are in the prison.